Work-Life Balance: Between Professionalism and Well-Being, the Role of Office Managers in Maintaining Employee Performance - Putri, Chrisantia Stella Amanda; Firdaus, Izza Tibta; Chaniago, Harmon (International Journal Administration, Business & Organization, 2025)
This study explores how office managers contribute to maintaining employees’ work-life balance to help sustain their performance. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings highlight that office managers play a key role in fostering a work environment that supports both mental well-being and productivity. Theoretically, this research supports the perspective within human resource management that work-life balance is a critical factor in employee performance. On a practical level, the insights from this study can inform organizations in designing flexible work policies, managing workloads more effectively, and enhancing managerial support. What sets this study apart is its focus on the role of office managers, an area often overlooked compared to that of senior management in bridging professional demands with employees’ personal needs. By doing so, it contributes to a contextual understanding of how middle management can help promote employee well-being in today’s evolving workplace.